PENERAPAN BUDI PEKERTI DALAM PROGRAM PEMBELAJARAN PPKN PADA MAHASISWA JURUSAN PPKN DI UNIVERSITAS NEGERI MEDAN UNTUK MENJADI MAHASISWA YANG BERINTEGRITAS - Simanjuntak, Johan; Siahaan, Ruth; Mangunsong, Al Firman; Yunita, Sri (Universitas Islam Negeri Alauddin Makassar, 2023)
Now that the education system has lost its true vision, most educational institutions now tend to take a pragmatic view, namely to produce work-ready graduates. After all, education does not only serve to prepare a qualified and competitive generation to find work. However, it must be endowed with noble moral values. Education is only oriented towards worldly life, so that the spiritual aspects of religion are neglected. From the above phenomenon, it is clear that currently there is a moral crisis that must be returned to the spirit of noble character education. This is in line with what Ki Hajar Dewantara fought for in his time about the concept of character educationThis study aims to determine the concept of character in the PPKN education program for Student of Pancasila and Citizenship Education, State University of Medan. The development of the concept of character is needed to form a PPKN education program. In this study, two research methods were used, namely qualitative research methods and quantitative research methods. so that researchers can conclude data sources according to their respective data collection techniques. Data collection instruments are in the form of questionnaires and open interviews. This research produces an understanding of success on the basis of understanding the concept of character in the Civics Education program.